Veinte años después de la publicación del Informe Final de la Comisión de la Verdad y Reconciliación - Villasante Cervello, Mariella (2024)
There has been no concern on the part of the State to educate young people about what Peru experienced between 1980 and 2000, nor has the work of the CVR been sufficiently valued. Since Fujimori’s time, a parallel history was created, and all the crimes perpetrated by the State, especially those whose main leader was Fujimori, remained unnoticed, hidden, despite the fact of being State crimes. But at least in the judicial field progress was made and it was one of the causes for Fujimori’s extradition and conviction. Furthermore, the forced disappearances were hidden, as far as the military leaders were concerned, by the State itself, because when the Ministry of Defense was asked for the names of the soldiers who had acted under pseudonyms, the CVR did not receive any names. Likewise, there is the Reparations Council for victims, created in 2006; Financial reparations have been made to individual and collective victims due to social pressure during the time of President García. But in moral reparations, education, and health, not much progress has been made. Those who have followed the IF better are the populations where there have been victims, they are the ones who best remember and vindicate the work of the CVR. Finally, where the most progress has been made is in the field of the arts, through films, theater, and literature.